A 'Foodshed' Moment for Planning: Investigating the Role of Food-Sensitive Planning in supporting Cape Town?s Resilience Strategy to strengthen Food Security, using the Philippi Horticultural Area as a case study - Zaloumis, Georgina (School of Architecture, Planning and Geomatics, 2024)
In recognition of the complexities and urgency brought about by increasing present and expected future intersectional crises, the CoCT developed and adopted its own Resilience Strategy. This strategy realises the fragility of urban food systems and the importance of achieving resilience to better support food security within Cape Town. Small-scale farms which make up the Philippi Horticultural Area (PHA) have been effective in retaining the production and accessibility of food which is resilient in the face of numerous shocks and stresses. It currently produces 50-70% of Cape Town's nutritionally dense and fresh food making it a vital component of Cape Town's foodshed. Additionally, it is also essential because it achieves multiple benefits across the Resilience Strategy due to its ecological, agricultural as well as socio-economic value to Cape Town. However, a proactive planning approach is needed as the PHA is under threat due to land-use pressures from mismanagement of land regulations, planning uncertainty and a lack adequate governance. Thus, there is a need to examine the role of food-sensitive planning in strengthening Cape Town's Resilience Strategy with achieving food security, using the PHA as a case study. This site provides an opportunity for planners to rethink how food-sensitive planning can be better integrated into the MSDF. The aim of the study is to investigate how the MSDF can better aligned with Cape Town's Resilience Strategy to mitigate threats to the PHA and enhance the resilience of local food production in Cape Town using food-sensitive planning. This aim will be achieved through desktop research, semistructured interviews, and field observations in the PHA. The results of this study indicate that foodsensitive planning is an innovative method to better harness and harmonise with the MSDF and Resilient Strategy to enable a more resilient food system in Cape Town. This is through the integration of bottom-up knowledge and top-down action to implement targeted interventions that value and protect food security assets such as the PHA. Nevertheless, going forward this research can contribute to studies around strengthening planning and governance of peri-urban agriculture areas in the global South to better support urban resilience and food security as well as broaden literature around food-sensitive planning.